Synopsis of the Neotropical Sclerodermus Latreille (Hymenoptera, Bethylidae) with description of a new species attacking human beings - Azevedo, Celso O.; Colombo, Wesley D. (Zootaxa, 2022)
We provide a Neotropical synopsis of the genus Sclerodermus Latreille. The genus is recognized by having the antenna with 11 flagellomeres, the head globoid or nearly so, the eyes present and flat, and the clypeal median lobe strongly angled and deeply separated from the lateral lobes. The strong polymorphism of having wings is an intra- and intergeneric feature and the macropterous specimens are diagnosed by having forewings with the pterostigma slender and only the R cell closed. In this synopsis we recognized seven previously known species: S. formicarius Kieffer, S. galapagensis Brues, S. iridomyrmicicola Bruch, S. macrogaster (Ashmead), S. soror Westwood, S. spilonotum Evans, and S. wilsoni Evans. The type-species, S. domesticus Latreille is also included, but their occurrence in the Neotropical Region is in doubt. Additionally, we discovered one more species, S. chicomendesi n. sp., which is described and illustrated, based on both sexes with molecular support. This species was found attacking a woman in her office in Porto Alegre, Brazil, where there was wood furniture with holes bored by beetles of the Ptinidae genus Tricorynus Waterhouse. We also provide a key to the Neotropical species of this genus and a discussion about species attacking human beings.